2015
DOI: 10.1159/000441222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Relevance of IgE Sensitization to Profilin in Childhood: A Multicenter Study

Abstract: Background: Little is known about the prevalence and clinical relevance of hypersensitivity to the plant panallergen profilin in children. Objectives: The present study aimed to investigate prevalence, risk factors and clinical relevance of profilin sensitization in a large cohort of Italian children of different ages living in different geographic areas. Methods: Children with pollen allergy enrolled by 16 pediatric outpatient clinics sited in three main geographic areas of Italy were studied. SPT were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
8
46
1
Order By: Relevance
“…In fact, a recent study conducted in Italy showed that 23% of pollen-sensitized patients had IgE antibodies to profilins [27] and frequent sensitization to cross-reactive pollen allergens has been reported for many countries such as the southern parts of Europe [7,21,28,29]. In fact, patients in Astana, Kazakhstan, are exposed simultaneously to pollen from several unrelated plant species due to a short summer period with copollination of trees, grasses, and weeds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study conducted in Italy showed that 23% of pollen-sensitized patients had IgE antibodies to profilins [27] and frequent sensitization to cross-reactive pollen allergens has been reported for many countries such as the southern parts of Europe [7,21,28,29]. In fact, patients in Astana, Kazakhstan, are exposed simultaneously to pollen from several unrelated plant species due to a short summer period with copollination of trees, grasses, and weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, it has been recently shown that this happens also with molecular allergens. Asero et al [12] found that results of specific IgE to Phl p 12 (grass profilin) and skin prick tests to natural profilin (Pho d 2), purified from date palm extract gave a concordant response in 91 % of cases. In asthmatic patients, exhaled breath biomarkers [13] may be useful for identifying allergic patients.…”
Section: Reviewmentioning
confidence: 99%
“…In the paper by Asero et al in this issue of International Archives of Allergy and Immunology [7], an epidemiological, multicenter study of the prevalence and clinical relevance of profilin in an Italian sample of pollen-allergic children is presented. The study was performed on a sample of 1,271 children recruited from across Italy.…”
mentioning
confidence: 99%
“…According to Asero et al [7], ‘early sensitization to profilin… might thus be an early biomarker of a strong atopic predisposition and therefore imply a more severe clinical history of pollen allergy'. Another interesting and practical piece of information is that the potential involvement of profilin in oral symptoms should be investigated, even in the preschool population.…”
mentioning
confidence: 99%
See 1 more Smart Citation